Characteristics of 29 novel atypical solute carriers of major facilitator superfamily type: evolutionary conservation, predicted structure and neuronal co-expression - Emelie Perland; Sonchita Bagchi; Axel Klaesson; Robert Fredriksson (Open Biology, 2017)
Solute carriers (SLCs) are vital as they are responsible for a major part of the molecular transport over lipid bilayers. At present, there are 430 identified SLCs, of which 28 are called atypical SLCs of major facilitator superfamily (MFS) type. These are MFSD1, 2A, 2B, 3, 4A, 4B, 5, 6, 6 L, 7, 8, 9, 10, 11, 12, 13A, 14A and 14B; SV2A, SV2B and SV2C; SVOP and SVOPL; SPNS1, SPNS2 and SPNS3; and UNC93A and UNC93B1. We studied their fundamental properties, and we also included CLN3, an atypical SLC not yet belonging to any protein family (Pfam) clan, because its involvement in the same neuronal degenerative disorders as MFSD8. With phylogenetic analyses and bioinformatic sequence comparisons, the proteins were divided into 15 families, denoted atypical MFS transporter families (AMTF1-15). Hidden Markov models were used to identify orthologues from human to Drosophila melanogaster and Caenorhabditis elegans. Topology predictions revealed 12 transmembrane segments (for all except CLN3), corresponding to the common MFS structure. With single-cell RNA sequencing and in situ proximity ligation assay on brain cells, co-expressions of several atypical SLCs were identified. Finally, the transcription levels of all genes were analysed in the hypothalamic N25/2 cell line after complete amino acid starvation, showing altered expression levels for several atypical SLCs.